First description of macropterous male and female of Cryphocricos latus (Heteroptera: Naucoridae) Usinger - Herrera, Federico (2013)
The macropterous male and female of Cryphocricos latus are herein described for the first time; both were collected in Alajuela, Costa Rica. Notes to separate this species from other macropterous species of the genus are given.